Growing Fish to Make Money in Africa - Brummett, Randall (World Bank, Washington, DC, 2012)
Rural development projects target food security and poverty alleviation. In Central Cameroon, a project providing extension of integrated farming technology to rural/subsistence farmers and to periurban/small-scale commercial farmers achieved increases in fish pond productivity, number of fish farmers, and net returns from aquaculture. However, gains for commercial farmers were larger and more sustainable, and at less cost, than for subsistence farmers. This smart lesson describes the project and some of the lessons it provided.